Long-term Outcomes of Childhood Onset Nephrotic Syndrome - Hjorten, Rebecca; Anwar, Zohra; Reidy, Kimberly Jean (Frontiers in Pediatrics, 2016)
There are limited studies of long-term outcomes of childhood onset nephrotic syndrome (NS). The majority of children with nephrotic syndrome have steroid sensitive nephrotic syndrome (SSNS). Steroid resistant nephrotic syndrome (SRNS) is associated with a high risk of developing end-stage renal disease (ESRD). Frequently relapsing and steroid dependent NS are associated with long term complications of immunosuppressant therapy, including cataracts, osteoporosis and fractures, obesity, impaired growth, and infertility. Even SSNS with few relapses may be at risk of some complications. There remain many gaps in our knowledge of long-term outcomes of childhood NS, and further study is indicated.